LOL with Syntax: Teaching Grammar through Western Memes - Maulina, Puput Anggun; Afri, Evan; Zulyani, Lidhya; Anwar, Rury Fadilah; Derin, Tatum (ITScience (Information Technology and Science), 2025)
This study aimed to analyze how Western memes were used as an innovative medium for teaching English grammar in the English as a Foreign Language (EFL) context. The study addressed the limited empirical synthesis on multimodal, humor-based resources for grammar teaching in digital learning environments. Using a systematic literature review guided by the PRISMA protocol, twenty five empirical articles published between 2020 and 2025 were selected from Scopus, Google Scholar, DOAJ, and ERIC databases. The review showed that meme based grammar instruction increased students’ motivation and emotional engagement and reduced learning anxiety through the integration of humor, visual supports, and culturally relevant content. The use of memes also fostered active participation and a more democratic classroom climate. However, the findings revealed age related differences: younger learners were more enthusiastic and readily aligned with meme culture, whereas older learners required clearer explanations of cultural references to benefit optimally. Overall, the synthesis indicated that Western memes were effective in enhancing grammatical understanding and long-term retention when implemented consistently and integrated with explicit instructional activities. These results suggested that memes could function not merely as entertainment but as a meaningful pedagogical tool that connects cognitive, affective, and social dimensions in English language learning. Implications for teachers and curriculum designers include the need to select culturally accessible memes and to scaffold their use with clear linguistic objectives